Синтез ограниченных по структуре оптимально-компромиссных стратегий обслуживания потока объектов - Куимова, А. С.; Федосенко, Ю. С. (НТУ "ХПИ", 2011)
Вводится модель однофазного обслуживания детерминированного потока объектов. Формулируется бикритериальная задача синтеза стратегий обслуживания. Показано, что учет ограничений на структуру стратегий обслуживания выводит задачу из класса NP-трудных и позволяет построить полиномиальный алгоритм синтеза стратегий, оптимальных по Парето. Приводится пример. Библиогр.: 8 назв.

In this paper a model of single-phase service of deterministic objects flow is discussed. A bicriteria problem of service policies synthesis is formulated. It is shown that if restrictions on service policies structure are imposed the problem will become non NP-hard and it will be possible to design a polynomial algorithm for Pareto-optimal service policies synthesis. Example is introduced. Refs.: 8 titles.
The synthesis of structure-bounded optimal compromise service policies of object flow
Keywords: бикритериальная модель; NP-трудность; оптимальность по Парето; service policies; NP-hardness; Pareto optimality